2012
DOI: 10.7197/1305-0028.1269
|View full text |Cite
|
Sign up to set email alerts
|

Neostigminin başarısız olduğu roküronyuma bağlı rezidüel kürarizasyonda sugammadeks kullanımı

Abstract: ÖzetNondepolarizan kas gevşetici ajanların etkilerinin uzamasına bağlı olarak gelişen postoperatif rezidüel kürarizasyon modern anestezide hala yaygın görülen ve hasta güvenliğine ciddi tehdit oluşturan önemli bir problemdir. Anestezi sonrasında rezidüel nöromusküler blok, uygun şekilde döndürülmezse postoperatif pulmoner komplikasyonların gelişimini ve postoperatif mortaliteyi arttırır. Spinal kitle nedeniyle opere edilen Amerikan Anestezistler Derneği II risk grubu olgumuzda nöromusküler bloker olarak roküro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Tuzcu et al [19] reported that upon the development of agitation, hypertension, tachycardia, and tachypnea at the end of the operation performed in a patient who received a combination of atropine-neostigmine, sedation with propofol was applied. Since the patient could not remove the effects of neostigmine and rocuronium, sugammadex was administered, and the case became completely stable 90 s later.…”
Section: Discussionmentioning
confidence: 99%
“…Tuzcu et al [19] reported that upon the development of agitation, hypertension, tachycardia, and tachypnea at the end of the operation performed in a patient who received a combination of atropine-neostigmine, sedation with propofol was applied. Since the patient could not remove the effects of neostigmine and rocuronium, sugammadex was administered, and the case became completely stable 90 s later.…”
Section: Discussionmentioning
confidence: 99%